2014
DOI: 10.1111/gwmr.12042
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chemical and Isotopic Signatures to Distinguish Between Uranium Mill‐Related and Naturally Occurring Groundwater Constituents

Abstract: Chemical and isotopic signatures were determined in groundwater samples to aid in distinguishing the source of contamination in three desert arroyos and a buried channel (the swale) near Shiprock, New Mexico. The contamination in the swale and one of the arroyos, Many Devils Wash, was previously attributed to a former uranium mill site because of the similar suite of contaminants (nitrate, selenium, sulfate, and uranium) and the close (0.8 km) proximity. The other two arroyos are far removed from the mill site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…For arsenic contaminated groundwater (pH 7.5), we prepared a synthetic Bangladesh groundwater (SBGW) electrolyte solution following a recipe derived from a British Geological Survey analysis of thousands of groundwater wells in Bangladesh [39]. For groundwater co-contaminated by uranium and nitrate (pH 3.5-5.5), which can occur at sites of uranium enrichment [37], we prepared two nitrate contaminated groundwaters (NO 3 -GW 1 and NO 3 -GW 2) that were made to mimic the composition of contaminated groundwaters reported previously [40][41][42][43][44]. Because of their trace concentrations, arsenic and uranium were excluded from the synthetic groundwater recipes.…”
Section: Preparation Of the Electrolyte Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For arsenic contaminated groundwater (pH 7.5), we prepared a synthetic Bangladesh groundwater (SBGW) electrolyte solution following a recipe derived from a British Geological Survey analysis of thousands of groundwater wells in Bangladesh [39]. For groundwater co-contaminated by uranium and nitrate (pH 3.5-5.5), which can occur at sites of uranium enrichment [37], we prepared two nitrate contaminated groundwaters (NO 3 -GW 1 and NO 3 -GW 2) that were made to mimic the composition of contaminated groundwaters reported previously [40][41][42][43][44]. Because of their trace concentrations, arsenic and uranium were excluded from the synthetic groundwater recipes.…”
Section: Preparation Of the Electrolyte Solutionsmentioning
confidence: 99%
“…Source waters with low chloride levels, alkaline pH and high concentrations of nitrate, carbonate and other high affinity oxyanions can be a barrier to high Faradaic efficiency. Treatment influents with such solution chemistry can be encountered in nitrate contaminated groundwater systems, including those impacted by agricultural runoff [57], sewage [58], and radionuclide enrichment activities [37,42,44]. Furthermore, chloride concentrations in groundwaters contaminated by geogenic arsenic can be low and…”
Section: Field Treatment Recommendationsmentioning
confidence: 99%
“…Uranium concentrations in the area varied from 1.5 µg/L to 9280 µg/L, with 32 of the 33 samples being above that of the MCL. 6 At high uranium concentrations in water there is potential for increased toxicological risk for the public. Exposure studies found that people exposed to high uranium concentrations in water (620 µg/L average) had an average uranium concentration of 0.162 µg/L in their urine (highest detected at 9.55 µg/L) several months after exposure.…”
Section: Uranium Legacy Contamination Within the Navajo Nationmentioning
confidence: 99%
“…where the solubility constant (K sp ) is related to the soluble species activity raised to the power of their molar coefficient. 27 This is compared to that of groundwater near Shiprock, NM that had concentrations of HCO 3 between ~100-1500 mg/L (pH's between 6.4 and 7.7) 6 where CO 3 2would be at ~ 0.5% of these concentrations (0.5-7 mg/L). At such high concentrations in surface waters and ground waters, carbonates can compete with uranium hydrolysis products, creating highly soluble uranyl carbonate species and contributing to enhanced mobility of uranium in the environment.…”
Section: Uranium Legacy Contamination Within the Navajo Nationmentioning
confidence: 99%
See 1 more Smart Citation